A Commentary on Poudrier's "Tapping to Carter: Mensural Determinacy in Complex Rhythmic Sequences" - Fischinger, Timo; van Dyck-Hemming, Annette (Empirical Musicology Review, 2018)
This paper is a brief commentary on Poudrier's (2017) research article titled "Tapping to Carter: Mensural Determinacy in Complex Rhythmic Sequences." Poudrier's study aimed "to explore the relative salience of an implied beat in two contrasting rhythmic sequences" (p. 277) taken from one of Elliott Carter's compositions using a pulse finding paradigm. In our commentary, we critically evaluate the current approach and discuss further interpretations based on the author's results. Primarily, we argue that it is very difficult to draw any clear conclusions from the data (on a mathematical/statistical basis) because the recorded tapping behavior, namely the overall synchronization rate of the participants was far below chance level. These results therefore need to be interpreted with caution, which also implies that emergence of temporal expectations in terms of the concept of "mensural determinacy," originally conceptualized by Hasty (1997), still needs further clarification. Nevertheless, this study may serve as a fruitful example for a pulse finding study, offering some helpful insights into the methodological issues when applying a tapping paradigm to highly complex art/modern music.